Bioconversion of Palm Oil Mill Effluent for the Production of Organic Acids and Polyhydroxyalkanoates - Abdul Rahman, Nor' Aini (2000)
In this study, palm oil mill effluent (POME) was utilized as a substrate for the production of polyhydroxyalkanoate (PHA) by Alcaligenes eutrophus. PHA production was achieved via a two-stage process; organic acids production from POME followed by PHA production from the organic acids. In the first stage, the study focused on optimisation of organic acids production as part of an integrated zero-emission system. Optimisation of organic acids production was performed by batch and continuous anaerobic treatments. In batch treatment, POME was mixed with different inoculum sizes (POME sludge) of 25%, 33%, 50% and 33% diluted sludge (two times) with tapwater in all conical flask. The result showed using inoculum size of 25%, 33% and 50% gave high organic acids production (7.0 g/L) after 4 days/of treatment.Continuous treatment was carried out at four different retention times (2.5, 5, 7.5 and 10 days). POME was mixed with an equal ratio of anaerobic POME sludge in a 12 L stirred-tank bioreactor. The pH was controlled at 7.0 to enhance organic acids production, particularly acetic and propionic. Total organic acids produced were 7.7 to 9.6 g/L for 2.5, 5 and 7.5 days retention times. More than 75% of the chemical oxygen demand (COD) conversion of POME was achieved during anaerobic treatment at 5, 7.5 and 10 days retention times. The best retention time was 5 days which produced 9.53±1.28 g/L of total organic acids, 11700 mg/L COD and 77% COD conversion of POME at steady state. After separation of the organic acids in the treated effluent by ion exchange chromatography, the residual COD of the effluent was less than 100 mg/L which met the effluent discharge standard set for the industry by the Department of Environment of Malaysia. The effluent collected during continuous anaerobic treatment at 5 days retention time was concentrated by evaporation to be used in the second stage for polyhydroxyalkanoate production. The results showed that by evaporation, the organic acids could be concentrated ten-fold to about 100 giL for use as substrates for the fed-batch fermentation. The concentrated organic acids were successfully converted to PHA by Alcaligenes eutrophus strain ATCC 17699 under a non-sterile fermentation system when the initial cell density was kept high at 4 g/L. After 150 hours, 20 g/L cells were obtained with more than 60% (gig) PHA content being produced.